2015
DOI: 10.1083/jcb.201408087
|View full text |Cite
|
Sign up to set email alerts
|

NORE1A is a Ras senescence effector that controls the apoptotic/senescent balance of p53 via HIPK2

Abstract: NORE1A is a Ras senescence effector that modulates HIPK2-dependent posttranslational modifications of p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
178
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(183 citation statements)
references
References 62 publications
(136 reference statements)
3
178
2
Order By: Relevance
“…In 2015, Donninger et al found that NORE1A over-expression induces senescence at levels comparable to those induced by activated Ras, and suppression of NORE1A both impairs senescence and enhances Ras-mediated transformation [17]. This correlates with Calvisi's finding that NORE1A expression in primary human tumors correlates with the expression of markers of senescence [123].…”
Section: Nore1a Was First Implicated As Having a Role In Ras-induced supporting
confidence: 71%
See 4 more Smart Citations
“…In 2015, Donninger et al found that NORE1A over-expression induces senescence at levels comparable to those induced by activated Ras, and suppression of NORE1A both impairs senescence and enhances Ras-mediated transformation [17]. This correlates with Calvisi's finding that NORE1A expression in primary human tumors correlates with the expression of markers of senescence [123].…”
Section: Nore1a Was First Implicated As Having a Role In Ras-induced supporting
confidence: 71%
“…Phosphorylation at residue Ser46 by HIPK2 promotes apoptosis, but HIPK2 can also recruit acetyltransferases to acetylate p53 at specific lysine residues to promote pro-senescence effects (Reviewed in [152]). NORE1A promotes the scaffolding of HIPK2 to p53, resulting in the suppression of Ser46 phosphorylation of p53 and the enhancement of p53 acetylation at lysine residues 382 and 320, which drive p53-dependent senescence [17]. Without the presence of p53, however, NORE1A still retained some ability to induce senescence, suggesting that NORE1A regulates senescence through a multifaceted process [17].…”
Section: Nore1a Was First Implicated As Having a Role In Ras-induced mentioning
confidence: 99%
See 3 more Smart Citations